Mucin Balls Influence Corneal Infiltrative Events. Issue 4 (April 2017) - Szczotka-Flynn, Loretta B.; Jiang, Ying; Stiegemeier, Mary Jo; Mutti, Donald O.; Walline, Jeffrey; Wilson, Tawnya; Debanne, Sara
ABSTRACT: Purpose: To determine whether mucin ball (MB) formation is protective against corneal infiltrative events (CIEs) as previously reported. Methods: Two hundred eighty-two eligible participants were enrolled at three sites in the USA. Participants began a 1-month continuous wear run-in period with high modulus lotrafilcon A lenses to assess their ability to form MBs (phase 1). Subsequently, they were stratified by this characteristic and randomized to balafilcon A or comfilcon A lenses for 7-day extended wear and followed for 1 year (phase 2). MB formation in each phase was defined as repeated presence of any MBs on a person level. Multivariable Cox proportional hazards regression was used to model the probability of a CIE as a function of MB formation in each phase and other covariates. Results: Of the 282 participants who entered phase 1, 218 of them entered the phase 2 randomized trial during which 33 CIEs occurred. Overall, 74%, 61%, and 79% of participants repeatedly produced MBs in lotrafilcon A, balafilcon A, and comfilcon A lenses, respectively. Early repeated MB presence in phase 1 with lotrafilcon A lenses significantly increased the rate of CIEs in phase 2 (12-month follow-up) by 466% (HR 4.66, 95% confidence interval 1.10–19.79, P = .0372). Repeated, longer-term MB presence during wear of balafilcon A or comfilcon A in phase 2 did not significantly reduce the incidence of CIEs; however, it significantly decreased the rate of CIEs by 62% (hazard ratio (HR) 0.380, 95% confidence interval 0.145–0.998, P = .0494). Conclusions: The overarching hypothesis that MB formation is protective against CIEs throughout extended wear was not supported. Although a protective effect of longer-term MB presence on rate of CIEs was detected, early-onset MB formation substantially increased the hazard for CIE in subsequent wear with different lens types.